1985
DOI: 10.1002/tea.3660220503
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the visuo‐spatial aptitude of students

Abstract: Research to date has not been able to agree whether visuo-spatial ability can be influenced through practice. Many have concluded that spatial awareness is an innate phenomena and cannot be learned. Others contend that an individual's visuo-spatial potentials are acquired through interactions with the environment. Many of these theorists believe that spatial thinking can be developed through interactive exercises devised to encourage mental image formation and manipulation. To help alleviate the confusion surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
14

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 17 publications
(10 reference statements)
3
57
0
14
Order By: Relevance
“…This finding supports the notion that males on average have one standard deviation higher spatial intelligence quotient than females 16 however other research has found no difference by gender 17 and identified that visuo-spatial aptitude can be enhanced through teaching 18 . It is perhaps the spatial aptitude that is important and not the gender; a subject for further research.…”
Section: Discussion 891supporting
confidence: 85%
“…This finding supports the notion that males on average have one standard deviation higher spatial intelligence quotient than females 16 however other research has found no difference by gender 17 and identified that visuo-spatial aptitude can be enhanced through teaching 18 . It is perhaps the spatial aptitude that is important and not the gender; a subject for further research.…”
Section: Discussion 891supporting
confidence: 85%
“…As pointed out in numerous studies (e.g. Bishop, 1978;Lord, 1985), all these circumstances are provoking an impoverishment of the spatial La habilidad espacial en las nuevas titulaciones técnicas La visión espacial y el uso del boceto como medio de expresión gráfica son capacidades fundamentales de todo ingeniero o arquitecto en el desempeño de su actividad profesional. En el proceso de diseño, mediante el empleo de croquis y bocetos se realizan sucesivas aproximaciones a la solución, gracias a la capacidad de visión espacial que permite tanto la realización de los bocetos como el razonamiento sobre los mismos.…”
Section: Spatial Ability In New Technical Degreesunclassified
“…Como ya ha sido puesto de manifiesto en numerosos estudios (Bishop, 1978;Kyllonen et al, 1984;Lord, 1985;McArthur & Wellner, 1996), todas estas circunstancias están provocando un empobrecimiento de las habilidades espaciales y de bocetado de los alumnos en relación a los planes de estudio tradicionales, lo cual origina a corto plazo dificultades en el aprendizaje de las materias relacionadas con la Geometría y con la Expresión Grá-fica, y a medio plazo una merma en la capacidad de diseño espacial en los alumnos próximos al egreso.…”
Section: Spatial Ability In New Technical Degreesunclassified
“…Although there are somewhat conflicting results in the literature regarding whether spatial ability can be improved, numerous studies (e.g., Ben-Chaim et al, 1988;Lord, 1985;Burnett & Lane, 1980) have indicated that it can be improved through training if appropriate materials are provided. As stated in the previous section, spatial relations tasks require one to imagine the rotations of 2D and 3D geometrical shapes, which can be found in many engineering drawing applications.…”
Section: How Can Spatial Ability Be Improved?mentioning
confidence: 99%